2022
DOI: 10.3892/br.2022.1544
|View full text |Cite
|
Sign up to set email alerts
|

Association of DNA methylation and genetic variations of the APOE gene with the risk of diabetic dyslipidemia

Abstract: Apolipoprotein E (APOE) is a key regulator of lipoprotein metabolism, and consequently, affects the plasma and tissue lipid contents. The aim of the present study was to investigate the parallel effects of APOE genetic variants and promoter methylation levels of six CpGs on the risk of diabetic dyslipidemia. A total of 204 Palestinian type 2 diabetes (T2D) patients (mean age ± SD: 62.7±10.2) were enrolled in the present study (n=96 with dyslipidemia and n=108 without dyslipidemia). Next generation sequencing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…(2015) demonstrated that the ApoE CpG island’s DNA methylation landscape is altered by the presence of the ɛ 4 allele in brain tissue, and this epigenetic change increases the risk of Alzheimer’s disease. In a separate study, Ereqat et al. (2022) discovered that SNPs (rs769446, rs449647, and rs405509) in CpG sites in the ApoE promoter were associated with the level of DNA methylation in peripheral blood cells and that there was a difference in DNA methylation at these CpGs between patients with diabetic dyslipidemia and controls.…”
Section: Discussionmentioning
confidence: 99%
“…(2015) demonstrated that the ApoE CpG island’s DNA methylation landscape is altered by the presence of the ɛ 4 allele in brain tissue, and this epigenetic change increases the risk of Alzheimer’s disease. In a separate study, Ereqat et al. (2022) discovered that SNPs (rs769446, rs449647, and rs405509) in CpG sites in the ApoE promoter were associated with the level of DNA methylation in peripheral blood cells and that there was a difference in DNA methylation at these CpGs between patients with diabetic dyslipidemia and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this, Leclerc et al reported that in murine models that c.+677 C>T variant was associated with MTHFR deficiency resulting in increased expression of pro-inflammatory HDL-C precursors and more significant lipid accumulation through alterations in the inflammatory response, lipid metabolism, and methylation capacity. 39 Until the exact mechanisms between MTHFR variants and lipid disturbances have not been fully understood, it could be related to altering methylation patterns in genes involved in lipid metabolism, 40 nevertheless, further research is necessary to understand the possible mechanisms involved in this alteration.…”
Section: Discussionmentioning
confidence: 99%